PENGGUNAAN MEDIA PEMBELAJARAN TIGA DIMENSI DALAM MENINGKATKAN PEMAHAMAN KONSEP MATERI JARAK TITIK, GARIS, DAN BIDANG PESERTA DIDIK DI SMK - LILIS ROKHAYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
Based on the phenomenon that we encounter in Mathematics Learning from Primary School to Upper Secondary School or Vocational High School, it is still not satisfactory. Mathematics learning tends to still be at the achievement of curriculum targets or books used as compulsory books. Learning is still dominated by teachers, where learners are more likely to accept the knowledge provided by teachers without the process of processing the existing potential. Learning does not emphasize on the understanding of the material studied and is not associated with the actual experience of the participants. In other words, the learning of mathematics is not meaningful because the learning has not been associated with the scheme that has been possessed by learners. Based on the above phenomenon, research was conducted on the use of three-dimensional learning media in improving the understanding of the concept of point distance, line, and field of XII OTKP-2 students in SMK Negeri 1 Bandung academic year 2021-2022. This research is a classroom action research that aims to improve students' understanding of mathematics learning concepts by using three-dimensional learning media on the material of point distances, lines, and fields in XII OTKP-2 class SMK Negeri 1 Bandung academic year 2021-2022. Each learner can use this three -dimensional learning media in accordance with their interests, and potential. Because the learning media used is the result of the learners themselves, it means that this learning media will be better understood by learners and more interested. ABSTRAKBerdasarkan fenomena yang kita temui dalam Pembelajaran Matematika mulai dari Sekolah Dasar sampai dengan Sekolah Menengah Atas atau Sekolah Menengah Kejuruan masih belum memuaskan. Pembelajaran Matematika cenderung masih pada pencapaian target kurikulum atau buku yang digunakan sebagai buku wajib. Pembelajaran masih didominasi guru, dimana peserta didik lebih cenderung menerima pengetahuan yang diberikan guru tanpa proses pengolahan potensi yang telah ada. Pembelajaran kurang menekankan pada pemahaman akan materi yang dipelajari dan tidak dikaitkan dengan pengalaman nyata peserta didk. Dengan kata lain, pembelajaran matematika belum bermakna karena pembelajaran belum dikaitkan dengan skema yang telah dimiliki oleh peserta didik. Berdasarkan fenomena di atas, dilakukan penelitian tentang penggunaan media pembelajaran tiga dimensi dalam meningkatkan pemahaman konsep materi jarak titik, garis, dan bidang peserta didik kelas XII OTKP-2 SMK Negeri 1 Bandung tahun pelajaran 2021-2022. Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan pemahaman konsep belajar matematika peserta didik dengan menggunakan media pembelajaran tiga dimensi pada materi jarak titik, garis, dan bidang di kelas XII OTKP-2 SMK Negeri 1 Bandung tahun pelajaran 2021-2022. Setiap peserta didik dapat menggunakan media pembelajaran tiga dimensi ini sesuai dengan minat, dan potensi yang dimilikinya. Karena media pembelajaran yang digunakan adalah hasil dari buatan peserta didik sendiri, artinya media pembelajaran ini akan lebih dipahami oleh peserta didik dan lebih tertarik.